Pengaruh Metode Demonstrasi Terhadap Hasil Belajar Siswa Pada Materi Sistem Koloid - Ijing Modeong; Desire A. S. Rumondor; Septiany Ch. Palilingan (Oxygenius Journal Of Chemistry Education, 2022)
The demonstration method is a method that can make students' attention more focused on what is being taught so that students are more active and do not feel bored in learning. This study aims to see the effect of the demonstration method on student chemistry learning outcomes on colloidal system material at SMA Negeri 1 Tutuyan in the 2020/2021 academic year. This research is a pre-experimental research with one group pretest-posttest design. The population in the study were all students of class XI IPA and the sample taken was class XI IPA MIA 1, totaling 30 people. Testing the hypothesis using the t-test formula at the significant level = 0.05. Based on the data analysis, the value of tcount = 23.90 and ttable = 2.045. The value of tcount > ttable then H1 is accepted and H0 is rejected, so it can be concluded that H1 is accepted, which means there is a significant difference between student learning outcomes on colloidal system material before and after using the demonstration method because there are differences. student learning outcomes. To find out how much the effectiveness of using the demonstration method is continued with the N-Gain test and obtained is 0.76 with high criteria.